The Role of Principal Support in Enhancing Educators' Mental Health and Work Productivity - Reza Murtisari; Ali Formen; Diana Diana (AL-ISHLAH: Jurnal Pendidikan, 2025)
The demanding workload and responsibilities faced by early childhood education (PAUD) teachers often contribute to mental health challenges, which in turn affect their productivity. Support from school principals is essential in fostering a healthy and effective educational environment. This study examined the influence of principal support on the mental health and work productivity of PAUD teachers in Semarang City. A total of 111 teachers were selected through purposive sampling using the Slovin formula with a 5% margin of error. The sample included only schools led by principals who do not simultaneously serve as teachers. Data were collected using a Likert-scale questionnaire distributed via Google Forms. Statistical analyses included tests for normality, significance, linearity, multicollinearity, heteroscedasticity, and multiple regression. The findings revealed that principal support has a significant positive effect on both the mental health and work productivity of PAUD teachers. Enhanced support from principals was associated with better mental well-being among teachers, which in turn led to increased productivity. Furthermore, the effect of principal support in maintaining teachers’ mental health accounted for 46.2% of the variance in their work productivity. Principal support plays a vital role in maintaining teachers’ mental health and enhancing their productivity. Strengthening leadership support within early childhood education settings can contribute to improved teacher performance and overall educational quality.